Assessing the risk of the food-energy-water nexus of urban metabolism: A case study of Kinmen Island, Taiwan. (March 2020) - Chen, I-Chun; Wang, Yi-Hsin; Lin, Wei; Ma, Hwong-wen
Highlights: FEW nexus risk is identified on urban metabolism by material flow analysis. A nexus risk assessment supports the design of optimal resource management. Risk tradeoffs between resources are assessed for a low resource region. Abstract: Implementing effective resource management is crucial for urban sustainability. Potential resource management strategies should be assessed under the framework of a resource nexus to avoid problem shifting. The urban metabolism of food, energy, and water is driven by lifestyle, industrial structure, and infrastructure. This study employed material flow analysis to identify resource metabolism through the phases of supply, process, demand, and final sink. The resource intensity of urban activities and the risk of the nexus of resources were quantified to illuminate management strategies. This study investigated the food-energy-water nexus (FEW nexus) for a small and multi-sector island city, Kinmen, and found that the nexus risk of water for food is the highest. Water and energy consumption have excessive loads on resource metabolism in a multi-sector city, and the main demand sectors increase the nexus risk in water for food. The results indicated that higher risk results from higher resource consumption intensity, particularly in areas of economic growth. Resource management of the FEW nexus needs the best tradeoff strategy to meet the goals of urban metabolism sustainability. The risk assessment framework can support the design of optimal resource management strategies to pursue urban sustainability. Consequently, given the limitations of water treatment technology, the impact of energy risk mitigation is poor (below 4% of energy risk in 2015) and the energy risk will continue to increase (by about 10% based on the economic activity). As a result, imported water is the best tradeoff strategy to meet the FEW nexus safety for Kinmen City as a low-resource and sightseeing activity area.